EFFICAS II: optimization of catheter contact force improves outcome of pulmonary vein isolation for paroxysmal atrial fibrillation - Kautzner, Josef; Neuzil, Petr; Lambert, Hendrik; Peichl, Petr; Petru, Jan; Cihak, Robert; Skoda, Jan; Wichterle, Dan; Wissner, Erik; Yulzari, Aude; Kuck, Karl-Heinz (Europace (London, England), 2015)
A challenge of pulmonary vein isolation (PVI) in catheter ablation for paroxysmal atrial fibrillation (PAF) is electrical reconnection of the PV. EFFICAS I showed correlation between contact force (CF) parameters and PV durable isolation but no prospective evaluation was made. EFFICAS II was a multicentre study to prospectively assess the impact of CF guidance for an effective reduction of PVI gaps. Pulmonary vein isolation using a radiofrequency (RF) ablation catheter with an integrated force sensor (TactiCath™) was performed in patients with PAF. Operators were provided EFFICAS I-based CF guidelines [target 20 g, range 10-30 g, minimum 400 g s force-time integral (FTI)]. Conduction gaps were assessed by remapping of PVs after 3 months, and gap rate was compared with EFFICAS I outcome. At follow up, 24 patients had 85% of PVs remaining isolated, compared with 72% in EFFICAS I (P = 0.037) in which CF guidelines were not used. The remaining 15% of gaps correlated to the number of catheter moves at creating the PVI line, quantified as Continuity Index. For PV lines with contiguous lesions and low catheter moves, durable isolation was 81% in EFFICAS I and 98% in EFFICAS II (P = 0.005). At index procedure, the number of lesions was reduced by 15% in EFFICAS II vs. EFFICAS I. The use of CF with the above guidelines and contiguous deployment of RF lesions in EFFICAS II study resulted in more durable PVI in catheter ablation of PAF.